-5=-7(x+3)-3x

Simple and best practice solution for -5=-7(x+3)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5=-7(x+3)-3x equation:


Simplifying
-5 = -7(x + 3) + -3x

Reorder the terms:
-5 = -7(3 + x) + -3x
-5 = (3 * -7 + x * -7) + -3x
-5 = (-21 + -7x) + -3x

Combine like terms: -7x + -3x = -10x
-5 = -21 + -10x

Solving
-5 = -21 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
-5 + 10x = -21 + -10x + 10x

Combine like terms: -10x + 10x = 0
-5 + 10x = -21 + 0
-5 + 10x = -21

Add '5' to each side of the equation.
-5 + 5 + 10x = -21 + 5

Combine like terms: -5 + 5 = 0
0 + 10x = -21 + 5
10x = -21 + 5

Combine like terms: -21 + 5 = -16
10x = -16

Divide each side by '10'.
x = -1.6

Simplifying
x = -1.6

See similar equations:

| 91-(6x+15)=6(x+4)+x | | 7x+17-5x+17=6 | | 21-8=x | | 5x-30=5x+30 | | 2m-m=13+16 | | 0.3(-0.9+8x)=3.2x | | 0.15-0.03(x+2)=-0.01(3-x) | | 1.33n+2n=-6.33+1.75n | | 8x+4x+7y=180 | | 2.4=14.4 | | 12x+(4x-1)=36 | | 1x+8=3 | | 7+9y=19-3y | | 12x-6x+204=12x+120 | | 2(d+7)= | | 6-2x(x+6)=3x+4 | | 6(2+5x)=12 | | 2a=a+11 | | -2-4x+8=-3(2-x)+4(8x+3) | | 8=8X+16+8X | | (x^4)+(x^2)-42=0 | | -91=9+8 | | 2y-4=2y-3 | | 52+180w=2(26+90w) | | 6x-5=1x+5 | | 2(8x+2)=3(2x-7)-5 | | 2(2-y)/5=-y | | 9v-4v=20 | | 3y-10=-2(6-y) | | 6(x+4)+3x-2=54 | | 2y-4=71-105y | | -208+11x=-5x+128 |

Equations solver categories